Sympathetic innervation of the mouse kidney and liver arising from prevertebral ganglia - Torres, Hayden; Huesing, Clara; Burk, David H.; Molinas, Adrien J.R.; Neuhuber, Winfried; Berthoud, Hans Rudolf; Münzberg, Heike; Derbenev, Andrei V.; Zsombok, Andrea (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2021)
The sympathetic nervous system (SNS) plays a crucial role in the regulation of renal and hepatic functions. Although sympathetic nerves to the kidney and liver have been identified in many species, specific details are lacking in the mouse. In the absence of detailed information of sympathetic prevertebral innervation of specific organs, selective manipulation of a specific function will remain challenging. Despite providing major postganglionic inputs to abdominal organs, limited data are available about the mouse celiac-superior mesenteric complex. We used tyrosine hydroxylase (TH) and dopamine β-hydroxylase (DbH) reporter mice to visualize abdominal prevertebral ganglia. We found that both the TH and DbH reporter mice are useful models for identification of ganglia and nerve bundles. We further tested if the celiac-superior mesenteric complex provides differential inputs to the mouse kidney and liver. The retrograde viral tracer, pseudorabies virus (PRV)-152 was injected into the cortex of the left kidney or the main lobe of the liver to identify kidney-projecting and liver-projecting neurons in the celiac-superior mesenteric complex. iDISCO immunostaining and tissue clearing were used to visualize unprecedented anatomical detail of kidney-related and liverrelated postganglionic neurons in the celiac-superior mesenteric complex and aorticorenal and suprarenal ganglia compared with TH-positive neurons. Kidney-projecting neurons were restricted to the suprarenal and aorticorenal ganglia, whereas only sparse labeling was observed in the celiac-superior mesenteric complex. In contrast, liver-projecting postganglionic neurons were observed in the celiac-superior mesenteric complex and aorticorenal and suprarenal ganglia, suggesting spatial separation between the sympathetic innervation of the mouse kidney and liver.
CRIS-Team Scopus Importer:2021-09-10
Keywords: iDISCO; Kidney; Liver; Retrograde tracing; Sympathetic nervous system